Effect of soil pH on sorption of salinomycin in clay and sandy soils - R. Jayashree; Shiv O. Prasher; Rajvinder Kaur; Ramanbhai M. Patel (African Journal of Environmental Economics and Management, 2019)
Salinomycin is polyether ionophore, commonly used in poultry industry for the prevention of coccidial infections and promotion of growth. A large amount of the administered antibiotic is excreted as parent compound, eventually reaching agricultural lands. This makes it imperative for researchers to understand the behavior of the compound in soil environment by conducting sorption-desorption studies. In this study, sorption of salinomycin was measured in four agricultural soils, a clay soil with low organic matter content (LOM), a clay soil with high organic matter content (HOM), a sandy soil with HOM, and a loamy sandy (LOM) soils, at three pH levels, namely 4, 7 and 9. Desorption studies was carried out using the batch equilibration technique. It was observed that more than 98% salinomycin was strongly sorbed by all soils, irrespective of the soil organic matter content or soil pH. The sorption of salinomycin to the sandy soil marginally increased as the pH decreased, while the sorption to the two clay soils marginally increased as the pH increased. Desorption of salinomycin with methanol over a 72 h period was < 0.2% of the amount added; however, it was > 70% with a phosphate buffer (pH 7). Since the phosphate buffer would mimic, to some extent, the quality of water flowing through field soils containing various salts, it was concluded that salinomycin could pose significant threats to both shallow ground water and surface water bodies.